Analisis faktor penentu keputusan pembelian konsumen pada online shop: peran penggunaan media sosial dan perilaku hedonis konsumen - Kurniawati, Kurniawati; Saputra, Ginanjar Wira; Diana, An Nisa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of the e-commerce business is currently showing significant growth. In addition, there are many millennial generations who behave consumptively. This of course did not appear out of nowhere, but with the development of the internet and social media. The increasing use of social media has led to consumer purchasing decisions online. This study aims to determine the effect of using social media and hedonic behavior on online purchasing decisions. This study uses a quantitative approach using explanatory. The sample was selected as many as 105 respondents from the Bandung College of Administrative Sciences. The results showed that there was an influence between the two variables, namely the use of social media and hedonic behavior on online purchasing decisions. This research also has implications for companies to review advertising through social media, given that currently social media users are higher, especially in today's younger generation.